MORPHOLOGICAL STRATEGIES IN NEWSPAPER DISCOURSE ON SEXUAL ALLEGATIONS: EVIDENCE FROM THE NATASHA–AKPABIO CASE IN NIGERIA - AGBU, David (International Journal of Arts, Languages, Linguistics and Literary Studies, 2025)
This research paper delves into the intricate dynamics of word formation in the context of sexual allegations involving prominent Nigerian figures, Natasha and Akpabio, as reported in various newspapers. The significance of this study lies in its exploration of how language shapes public perception and discourse on sensitive issues such as sexual misconduct. The primary objective is to analyze the linguistic strategies employed in newspaper headlines and articles, focusing on the word formation processes such as compounding, derivation, and clipping. The research employs a qualitative approach, analyzing fifteen excerpts from three major Nigerian newspapers. The findings reveal that the choice of words not only reflects the gravity of the allegations but also influences public sentiment and the framing of the narrative. This study contributes to the field of linguistics and media studies by highlighting the power of language in shaping societal attitudes towards allegations of sexual misconduct.